The Impact of Environment on Speaking Skills in 4 Year Old Children - Angelina Kurnia Juita; Veronika Owa Mere (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
Speaking skills are the skills or abilities of a person in conveying ideas, ideas, thoughts and feelings to others using spoken language clearly, correctly and can be understood by others. Speaking skills are closely related to the family environment and the school environment. A less supportive environment greatly affects children's speaking skills. This study aims to describe the impact of the environment on speaking skills in 4-year-old children in Simpang Kepuh RT 07 RW 10 Sukun sub-district, Malang city. The type of research used in this study is qualitative with a case study method with the research subject totaling one girl. Data collection techniques using observation, interviews and documentation. The data analysis technique uses qualitative descriptive analysis techniques which include data reduction, data presentation, and ends with drawing conclusions. Data validity techniques using extended observation and source triangulation. The results showed that the environment has an impact on children's speaking skills. The environment in question is a family environment and a school environment that does not stimulate children's speaking skills.